Prevalence of Diastasis Recti Abdominis in a Gynecological Population: A Cross-Sectional Study - Asma Ameer, Huma Waqar, Shanza Ayub, Aqsa Ilyas, Bilal Umar. Sara Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diastasis recti is the divarication of rectus abdominal muscles due to the splitting of the mid-line collagen structure called the linea alba. It results in poor body biomechanics and alteration in the center of gravity of the body. It occurs mostly in multiparous females and in those who have poorly toned abdominal musculature. Physical activity and maternal care are significant to resolve this condition. Objective: The purpose of the study is to substantiate the prevalence of diastasis recti in a sample of immediate post-partum females attended by the Allied Hospital of Faisalabad. The aim is to create awareness of DRAM in clinical settings and the general population. Study design: This is a cross-sectional study that included 90 samples of females in the immediate postpartum period. Methodology: Specific assessment was done by finger-width method manually and confirmed the presence of DRAM. The umbilical region was the set point from which measurements were taken. Results and Conclusions: The separation was present and mostly affected the multiparous females. The study showed 63.3% prevalence and normal rectus abdominis is 36.7%. It also verified that 42.2% of females suffered from DRAM above the navel out of 63.3% and the rest are below the umbilicus. DRAM was prevalent to be in the majority of post-partum females. It was more present in the supra-umbilical region. Keywords: Pregnancy, rectus abdominis, multiparous, primiparous, physiotherapy.